Sky‐Blue Organic Light Emitting Diode with 37% External Quantum Efficiency Using Thermally Activated Delayed Fluorescence from Spiroacridine‐Triazine Hybrid. Issue 32 (6th June 2016) - Lin, Ting‐An; Chatterjee, Tanmay; Tsai, Wei‐Lung; Lee, Wei‐Kai; Wu, Meng‐Jung; Jiao, Min; Pan, Kuan‐Chung; Yi, Chih‐Lung; Chung, Chin‐Lung; Wong, Ken‐Tsung; Wu, Chung‐Chih
Abstract : Extremely efficient sky‐blue organic electroluminescence with external quantum efficiency of ≈37% is achieved in a conventional planar device structure, using a highly efficient thermally activated delayed fluorescence emitter based on the spiroacridine–triazine hybrid and simultaneously possessing nearly unitary (100%) photoluminescence quantum yield, excellent thermal stability, and strongly horizontally oriented emitting dipoles (with a horizontal dipole ratio of 83%).